„Tyle wiemy o sobie/ile nas sprawdzono”. Recepcja Wisławy Szymborskiej w mediach - Wojtyra, Marta (Z Teorii i Praktyki Dydaktycznej Języka Polskiego, 2019)
The author presents the reception of Wisława Szymborska’s work. She shows how the Nobel Prize received by the writer in 1996 caused a sudden increase in interest in her work. This interest has been shown from two perspectives: one is a fascination with poetry and an attempt to put the Nobel Prize winner on a monument, against which the poet herself strongly protested, and the other is the perspective of an open reluctance, not to say hate, resulting from indicating Szymborska’s youthful fascination with the ideals of socialism. The article shows how the Internet has become a platform that has helped to promote, above all, the knowledge about the author of the poems and, to a lesser extent, reflection on her work.